Current account dynamics and the housing boom and bust cycle in Spain - Daniel Maas; Eric Mayer; Sebastian Rüth (University of Würzburg, Department of Economics, 2015)
We investigate the drivers of the negative correlation between housing markets and the current account in Spain. By employing robust sign restrictions, which we derive from a DSGE model for a currency union, we analyze the effects of domestic pull and foreign push factors in the mixed frequency VAR framework. Savings glut, risk premium, and house price expectations shocks are capable of generating the negative co-movement of housing markets and the current account in the data. In contrast, and counter-factual to the Spanish housing boom, financial easing shocks predict a decline in residential investment. Among the four identified shocks, savings glut shocks have most explanatory power for real house prices, residential investment, and the current account. We also reveal an important role of risk premium and house price expectations shocks for housing markets, whereas financial easing shocks do not explain sizeable fluctuations in the key variables.
Keywords: E32; F32; F45; 330; current account; housing markets; monetary union